PENGELOLAAN ASET DAERAH DALAM RANGKA MEMPERTAHANKAN WAJAR TANPA PENGECUALIAN (WTP) DI KABUPATEN KAMPAR - Hadinur Rahman, Meyzi Heriyanto, Tri Sukirno Putro (JIANA ( Jurnal Ilmu Administrasi Negara ), 2020)
Regional Asset Management in the context of maintaining Fair Without Exception (WTP) in Kampar Regency. The management of regional fixed assets belonging to the Kampar Regency's Revenue, Financial and Asset Management Office in coordinating the management of regional fixed assets in terms of performance accountability is not optimal, there are still many asynchronous asset values, inventory and reporting and control systems that have not been good.This study aims to Analyze the management of Regional Assets in order to maintain Fair Without Exceptions (WTP) in Kampar District and Analyze the factors that influence the management of Regional Assets in order to maintain Fair Without Exceptions (WTP) in Kampar District. This study uses the Theory of Regional Goods Management according to Regulation of the Minister of Home Affairs Number 17 of 2007 concerning Technical Guidelines for the Management of Re-gional Property. This type of research is a descriptive study with a qualitative approach. Data col-lection method is done by interview, observation and documentation. The results of this study in-dicate that the Management of Fixed Assets / Regional Property carried out by the field of assets in the financial management body and regional assets in order to maintain PAPs in Kampar Regency, as assistant managers have done the maximum and in accordance with the system and procedures for the management of regional property cycles as regulated in PERMENDAGRI No. 19 of 2016 concerning guidelines for the management of regional property but not all have been implemented to the maximum such as late submission of reports at the level of goods users (SKPD), the utiliza-tion of BPKAD's regional belongings Kampar Regency is limited to the use of borrow and use, se-curity carried out by BPKAD Kampar Regency does not do legal safeguards. Factors that influ-ence in maintaining WTP are HR factors because the need for knowledge and understanding of HR in managing fixed assets, leader commitment and asset valuation factors are also constraints, especially valuation of assets for which procurement is unknown.